PERUBAHAN PENGALAMAN HIDUP SEHARI-HARI DAN PERKEMBANGAN BERBAGAI DISIPLIN ILMU - Sujarwo, Sujarwo (Dinamika Pendidikan, 2015)
These days growth of science don't taken place on the spur of the moment, but happened step by step and evolutif. Therefore to understand growth of science. have to did division of phase or classification periodical. The each of period growth of science always for the individuality selected. To Basic change oflife experience and growth' of science. seen existence of acceleration of chang« civilization of human requirement to life enough, Matter this because of existend medium and facility which progressively sophisticated. The moral attitude of society which hunger for the progress, The accomplishment nutrition for the the ri.liillggeneration which good enough. so that havefor the ability strong which physical and good which brain. But on the other side. aspect spiritual and Nfl' style progressively materialistik which push the life consumtifand hedosnistir. Condition of this need the science growth which together with cultivation system of value the strong in society. Invention as early construct's science if which do the human until now don't onlv do by alone or the reglona! selected. but s,ilI influence by dimension time. space and cultural. Keyword' Invention. lift, experience and growth of science